Aerodynamic drag area of cyclists determined with field-based measures - Martin, J. C.; Gardner, A. S.; Barras, M.; Martin, D. T. (Sportscience, 2006)
Aerodynamic drag is an important factor in the performance of competitive track and road cyclists. Recently we used wind-tunnel testing to validate a practical measure of aerodynamic drag derived from a field test. We present here instructions for performing the field test on a straight flat road or in a velodrome, and we include a spreadsheet for performing the calculations.